APLIKASI METODE MODIFIKASI ICOLD UNTUK PENILAIAN KELAS RESIKO BENDUNGAN TAPIN - Rosmita Annisa; Ignatius Sriyana; Sri Sangkawati (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2021)
The risk assessment of the dam is carried out to estimate the hazard risk of the dam. Risk assessment on dams that have been built and in operation aims to determine the priority of repair and rehabilitation work to improve safety based on the risks that exist in the dam. Research on the risk class assessment of Tapin Dam using the modified ICOLD method includes calculating the risk value on various factors considered, namely the technical physical condition of the dam and related to the implementation of dam safety. The parameters of each factor were obtained from the results of field inspections and technical documents related to the Tapin Dam. Based on the results of the risk assessment, Tapin Dam is classified as a dam with a high risk class. Monitoring the behavior of the dam, regular inspections and post-earthquake conditions, performing routine and periodic maintenance, as well as updating and socializing the RTD are actions that the Tapin dam administrator can take to manage long-term risks that can occur.